A retrospective review of the common childhood illnesses and the indications for antibiotic prescription at community hospital in Malawi - Lubanga, Adriano Focus; Khuluza, Chana; Muhyuddin, Jamillah; Simfukwe, Reuben; Kaphesi, Frank; Yeum, Yeo Hwan; Yoon, Joshua J.; Kim, Changwoo; Kim, Seunghyun; Kim, Si Yeon; Lee, Ji An; Park, Jooheon; et al. (Frontiers in Antibiotics, 2024)
Background Childhood remains a vulnerable period and a key determiner for adult health. Various illnesses experienced by children in their early years determine future performance and contribution to society. Acute and chronic infectious diseases, undernutrition, and early childhood non-communicable diseases have greatly been linked to intellectual disability, poor childhood development, increased morbidity, and household and healthcare economic costs. In most developing countries, infections contribute to a larger burden of disease. Despite this being the case, most developing countries have a limited range of diagnostic capacity and access to a wide range spectrum of WHO Access, Watch and Reserve antibiotics. This leads to overuse and misuse of the available antibiotics and a wide range spread of resistance strains. In this study, we evaluated common childhood presentations and indications for antibiotic prescriptions at a community hospital in Malawi. Objective This study analyzed common childhood Clinical Presentations and antibiotic prescription patterns at the pediatric outpatient department (OPD) at St. Gabriel Community Mission Hospital in Malawi. Methods A retrospective search of all outpatient routinely corrected data from St. Gabriel Community Mission Hospital between January to December 2022 was carried out. Manual screening was done on all appropriate routines under 14 medical records, and prespecified variables were extracted. Data collected consisted of total OPD patient number, age, sex, diagnosis and prescription. Results A total of 2711 children under 15 years of age were included, with 53.9% being males. The majority of them were below the age of 5 (59.5%). 30% of the cases seen in the department were attributable to respiratory presentation, representing the majority of the cases seen. Sepsis and enteric diseases also constituted the majority of the cases seen and contributed 18% and 7% respectively. 68% per cent of the children seen during the period of the study had an antibiotic prescription, with the majority having only one antibiotic prescribed (31.7%). Overall, amoxicillin constituted the most commonly prescribed antibiotic for the whole system, while metronidazole was the most commonly prescribed antibiotic among enteric illnesses. Being under five was associated with a higher likelihood of antibiotic prescription (p <0.001). There were no significant differences in antibiotic prescription by gender and prescribing quarter of the year. Conclusion Our findings suggest that there could be overuse and misuse of antibiotics within community hospitals. Overuse and misuse of antibiotics at the community level is closely linked to limited cytobacteriological testing, and limited access to all categories of antibiotics. Amid limited resources, more research is needed to understand the barriers and facilitators toward appropriate and inappropriate antibiotic prescriptions among primary healthcare workers. Furthermore, more training is needed on the use of validated antimicrobial treatment guidelines and point-of-care rapid diagnostic tests to improve rational antibiotic use.